Assessment of somatic and motor development level of 10-12 year old children - Michał Spieszny; Karol Görner; Adam Jurczak (Kazimierz Wielki University, 2017)
SUMMARY Introduction. Therefore, the main aim of this dissertation is an assessment of the somatic and motor development of ten to twelve-year-old children from Polish families who live in London and a comparison of the results with the analogical measurements children live in Poland. Material and methods. The material of the research are the results of the measurements of 113 children of Polish origin who live in London and 151 children who live in Poland. The research was performed in the autumn of 2012. Chosen somatic features (body height, body mass, lean body mass - LBM, the percentage of fat in the body) and the level of motor skills (measured by the use of chosen tests of the European Physical Fitness Test - EUROFIT: running speed, abdomen muscles force, shoulders force, static force, spine flexibility) were analyzed. Results. There are significant differences between the body composition of children from Polish families who live in London and of those who live in Poland. Eleven and twelve-year-old children from London are characterized by a significantly higher percentage of fat in the total body mass than the children who live in Poland. Although children from London do not have a lower level of body height and mass than the children from Poland, they are characterized by a significantly lower level of motor skills, which was visible especially in case of speed, power endurance, explosive power and flexibility.   STRESZCZENIE Wstęp. Za główny cel pracy przyjęto próbę oceny poziomu rozwoju somatycznego i motorycznego 10-12-letnich dzieci z rodzin polskich mieszkających Londynie oraz porównanie wyników badań z analogicznymi pomiarami dzieci mieszkających w Polsce. Materiał i metody badań. Materiał opracowania stanowią wyniki pomiarów 113 dzieci pochodzenia polskiego mieszkających w Londynie oraz 151 dzieci mieszkających w Polsce. Badania przeprowadzono jesienią 2012 roku. Analizie poddano poziom wybranych cech somatycznych (wysokość ciała, masę ciała, masę ciała szczupłego - LBM, procentową zawartość tłuszczu w organizmie) oraz poziom sprawności motorycznej mierzonej przy zastosowaniu wybranych prób Europejskiego Testu Sprawności Fizycznej - EUROFIT (szybkość biegowa, siła mięśni brzucha, siła ramion, siła statyczna, gibkość kręgosłupa). Wnioski. Wystąpiły wyraźne różnice w zakresie składu ciała pomiędzy dziećmi z rodzin polskich mieszkających w Wielkiej Brytanii a badanymi w kraju. U dziewcząt i chłopców w wieku 11 i 12 lat z Londynu znacząco większy niż u rówieśników z polskiej grupy porównawczej był udział masy tłuszczu w ogólnej masie ciała. Dzieci mieszkające w Londynie, choć nie ustępowały poziomem wysokości i masy ciała rówieśnikom z Polski to charakteryzowały się znacznie niższym poziomem sprawności motorycznej, co szczególnie widoczne było w zakresie szybkości, wytrzymałości siłowej, a także siły eksplozywnej i gibkości.